Synthesis of cytotoxic spirocyclic imides from a biomass-derived oxanorbornene. (1st January 2021) - Lawrenson, Stefan B.; Pearce, Amanda K.; Hart, Sam; Whitwood, Adrian C.; O'Reilly, Rachel K.; North, Michael
Abstract: N -Substituted derivatives of cantharimide and norcantharimide represent a promising but underutilized motif for therapeutic applications. Herein, we report a divergent strategy for the preparation of secondary amides and norcantharimide-resembling spirocyclic imides from a biomass-derived oxanorbornene and assess their biological activity. Computational modelling suggests these compounds fall perfectly within lead-like chemical space (200 Da < RMM < 350 Da,  −1 < AlogP < 3), with the spirocyclic imides preferred due to their lack of reactive functionalities. Biological analysis of the spirocyclic imides revealed that the compounds displayed antiproliferative activity against a range of human cancer cells (A549, HCT 116, OVCAR-3, MDA-MB-231, MCF7 and PC-3) with the N- octyl derivative displaying the greatest potential as a potent broad-spectrum anticancer drug. Dose-response curves for the N- octyl spirocyclic imide found EC50 values of 56–95 μM dependent on the cell line, with highest activity against human colorectal carcinoma cells (HCT 116). Graphical abstract: Image 1